Lack of association between food insecurity, eating disorders, and orthorexia nervosa: findings from a cross-sectional study in Lebanon - Sacre, Hala; Haddad, Chadia; Rizk, Rana; Karam, Joanne; Salameh, Pascale (Frontiers in Public Health, 2025)
ObjectivesTo investigate the association between food insecurity (FI), eating disorders (EDs), and orthorexia nervosa (ON) among Lebanese university students.MethodsThis cross-sectional study, conducted between 2021 and 2022, enrolled 197 students, from various majors, via snowball sampling. Data were collected on Google Forms via social media platforms.ResultsMost participants (59.4%) declared being food-insecure, without financial support (67.0%), nor financial independence (68.5%). Most did not show any ED (81.7%) or a risk of ON (79.7%). Reported EDs were bulimia-nervosa (6.1%) and anorexia-nervosa (6.1%); 4.1% had a high risk of ON. No significant associations were found between declared FI, ED, and the risk of ON. Higher adherence to the Mediterranean diet (ORa = 1.31) and higher perceived stress (ORa = 1.14) were significantly associated with EDs. Higher exercise addiction scores (ORa = 1.25) and higher insomnia levels (ORa = 1.26) were significantly associated with the risk of ON. Being employed (ORa = 0.17) and skipping meals (ORa = 0.20) were inversely associated with declared ON.ConclusionFI and EDs were not associated among university students in Lebanon. Research into underlying mechanisms and cultural aspects is crucial to clarifying these associations.